THE IMPACT OF THE WITHDRAWAL OF UNITED STATES MILITARY TROOPS ON FOOD SECURITY IN AFGHANISTAN IN 2021-2022 - Izza, Atina; Basuki, Luthfi Wahyu (Journal of Social Political Sciences, 2024)
This study analyzes the impact of the United States' armed military invasion of Afghanistan, initiated after the 9/11 tragedy, on food security in Afghanistan during the years 2021-2022. The research employs a qualitative approach, interpreting data through a descriptive method using literature review from articles, journals, and related scientific studies. The theoretical framework integrates Hegemony Theory to examine U.S. power in Afghanistan and Food Security Theory to assess the food security situation in Afghanistan during 2021-2022. The U.S. military invasion in Afghanistan resulted in economic, food, and political instability, placing the country under significant food security threats, exacerbated by geographic challenges that hinder economic recovery. After the full military withdrawal by the U.S. in 2021, driven by a shift in foreign policy prioritizing diplomacy, alongside critiques of the U.S. occupation and the "America First" policy under Donald Trump, nearly 11 million Afghans remained in critical food insecurity. This number rose to almost 20 million by 2022. International trade conducted by Afghanistan in 2021 had no significant effect on improving the domestic economy. Therefore, the study concludes that the U.S. military withdrawal did not improve Afghanistan's food security, as underlying issues such as geographic conditions and political instability remained the primary factors affecting the country's food security situation.